Intelligent Learning Environments: The Case of Geometry - Laborde, Jean-Marie (NATO ASI series. Computer and systems sciences, 1996)
This book is based on a NATO workshop for researchers concerned with the design of intelligent learning environments for geometry. Geometry cannot bereduced to procedural knowledge and its complexity makes it of interest for the development of intelligent tutoring systems. The central theme of the volume is student modeling, which has three aspects: modeling the knowledge domain, modeling student knowledge, and designing the didactic interaction and learner control. Four main issues runthrough the papers in the book: - Knowledge about geometry is not real-world knowledge and its computer implementation implies a reification of geometry. - The learning of geometry involves conceptualization at a number of different levels, which must be reflected when modeling student knowledge. - The design of the interface and the management of the didactic interaction must cope with multiple representations. - Domains of geometry other than plane geometry are considered. The book is part of the NATO Special Programme on Advanced Educational Technology.